The effectiveness of the action-oriented approach in the teaching of the plural -s, possessive-s and third person singular inflectional endings to improve the speaking skills of seventh graders at Colegio Ambientalista de Pejibaye, Jiménez - Rojas Sánchez, Ismael 1992-; Salehi Cedeño, Sara 1994-; Solano Porras, María del Carmen 1990-; Ortega Cordero, Alfredo 1977- (Paraíso, [Cartago, Costa Rica], 2020)
This research analyzes whether or not the Action-Oriented Approach was effective for teaching the inflectional endings plural -s, possessive -s and third person singular in order to improve the speaking skills of a group of high school students (7th graders) at Colegio Ambientalista de Pejibaye, Cartago, Costa Rica. The purpose of the investigation rose from the necessity of knowing the reality about the effectiveness of the implementation of this new approach during academic English lessons. This study was focused on the development of this new approach by the design and the application of six sessions that involved the development of the Action-Oriented Approach in a real classroom of seventh graders. The level of the groups was chosen because during primary school, they had no contact with this new approach. For this investigation, a quasi-experimental design was chosen because the groups (7-2 and 7-3) were already established by the high school since the beginning of the year. Before implementing the teaching sessions, an observation was done in order to verify that the principles of the Action-Oriented Approach were applied by the cooperating teacher. The teaching sessions were planned by the researchers according to the Action- Oriented Approach for the experimental group and the Communicative Approach for the control group. Then, two oral tests (pre and post) were applied by the researchers to measure participants' initial and final performance, and six teaching sessions (each session consisted of three lessons of forty minutes per week for a total of eighteen lessons. These sessions were supposed to be carried out in seven weeks, but because of extracurricular activities, it took 14 weeks). Another group was selected which represented the control group (dealt with a different approach: the Communicative Approach). The results suggested a higher performance by the experimental group after being intervened, and an analysis on how participants...
Esta investigación analiza si el Enfoque Orientado en la Acción fue efectivo para enseñar las terminaciones de inflexión plural -s, posesivo -s y tercera persona singular para mejorar las habilidades de habla de un grupo de estudiantes de secundaria (7º grado) en el Colegio Ambientalista de Pejibaye, Cartago, Costa Rica. El propósito de la investigación surgió de la necesidad de conocer la realidad sobre la efectividad de la implementación de este nuevo enfoque durante las lecciones de inglés académico. Este estudio se centró en el desarrollo de este nuevo enfoque mediante el diseño y la aplicación de seis sesiones que implican el desarrollo del Enfoque Orientado a la Acción en un aula de alumnos de séptimo grado. Se eligió el nivel de los grupos porque durante la escuela primaria no tenían contacto con este nuevo enfoque. Para esta investigación, se eligió un diseño cuasi experimental porque los grupos (7-2 y 7-3) ya estaban establecidos por el centro educativo desde el comienzo del año. Antes de implementar las sesiones de enseñanza, se realizó una observación para verificar que los principios del Enfoque Orientado en la Acción estaban siendo aplicados por la persona docente a cargo de los grupos. Los investigadores planificaron las sesiones de enseñanza de acuerdo con el Enfoque Orientado en la Acción para el grupo experimental y el Enfoque Comunicativo para el grupo de control. Luego, los investigadores aplicaron dos pruebas orales (antes y después) para medir el rendimiento inicial y final de los participantes, y seis sesiones de enseñanza (que consistieron en tres lecciones de cuarenta minutos por semana para un total de dieciocho lecciones, que se suponía que se llevarían a cabo en siete semanas, pero debido a las actividades extracurriculares, tomaron catorce semanas) fueron realizadas por los investigadores. Se seleccionó otro grupo y representó al grupo de control (se ocupó de un enfoque diferente...
Proyecto de graduación (licenciatura en enseñanza del inglés)--Universidad de Costa Rica. Sede del Atlántico. Recinto de Paraíso. Carrera Enseñanza del Inglés, 2020
Keywords: INGLES -- GRAMATICA -- ENSEÑANZA SECUNDARIA; COMUNICACION ORAL